Közlekedésfejlesztés geopolitikai szemszögei két szomszédos ország példáján - Kovács, Áron (Közép-Európai Közlemények, 2017)
The study aims to identify factors that influence the development of transport sub-sectors, necessary changes in order to enhance the positive influence of traffic in the regions, and options for connections between individual modes of transport (sub-sectors). The complex transport network (TRANS) indicator and 9 social and economic indicators have been utilized for the empirical analysis (of data available in the Yearbooks of the Hungarian and the Serbian Central Statistical Office). The index makes it easy to compare the infrastructure levels of various transport networks. In addition, visualising regional differences makes it easier to compare them with other regional characteristics. The analysis shows the regional development of transport subsectors in Hungary and Serbia, and indicates the strength and direction of the relationship between various economic and social indicators. The interactions between economic and social indicators and the development of transport have been revealed by correlation analysis. The regions are arranged in groups by cluster analysis to indicate similarities and differences in their levels of development. This cluster analysis also revealed the extent of the difference between the regions of the two countries.